Microbial community structure variability over the development of healthy and underperforming oyster larval hatchery broods - Cram, Jacob A.; McCarty, Alexandra J.; Willey, Stacey M.; Alexander, Stephanie T. (Frontiers in Aquaculture, 2024)
Hatcheries nationwide suffer from unexplained acute production failures, termed crashes. The microbiota of oysters relates to larval health with previous studies showing that some bacterial species have positive and others negative effects on oyster health. To investigate microbial correlates of crashes, we collected samples from every batch of oyster larvae (Crassostrea virginica) produced by the Horn Point Laboratory Oyster Hatchery since 2021 and analyzed the microbiota of 15 of those batches over their duration in the hatchery, from age of 3 to 5 days until either harvest or complete die off of the batch. Across events, die-offs generally became evident at or after six days of age. We found that the microbiota of oyster larvae appears to respond to die-off events with crashed batches having fundamentally different microbiota than good batches at age 7 to 9 and 9 to 12 days. Crashed batches were often taken over by microeukaryotes and bacterial taxa from the Protobacteria and Bacteroidetes phyla. However, this presumably opportunistic community differed between batches. Observed Vibrio species level groups did not appear to be oyster pathogens and appeared to respond to, rather than precede, crashes.The microbiota of 3 to 5 day old larvae were statistically related to whether a die-off occured later in the larval batches' life, only when the taxa were first agglomerated to family level. The detection of two microbial species not previously known to associate with oysters, along with an increased presence of Dinophyceae, predominantly the toxin-producing Gyrodinium jinhaense, in 3 to 5 day old oyster larvae was statistically linked with subsequent batch crashes.This study suggests that the health of larval oysters shapes their microbiome. Conversely, it provides hints that the microbiome of larvae, and perhaps harmful algae, may drive hatchery crashes.